Role of free living, immobilized and non-viable biomass of Nostoc muscorum in removal of heavy metals: An impact of physiological state of biosorbent - Dixit, S.; Singh, D. P. (Cellular and Molecular Biology, 2014)
Biosorption of Pb and Cd by using free living, immobilized living and non-viable forms of Nostocmuscorum was studied as a function of pH (3-8), contact time (5-240 min) and metal concentration (10-100 µg ml-1), to find out the most efficient physiological formfor metal removal. Results revealed that optimum conditions for biosorption of both the metals by different states of biosorbentwere almost same (contact time- 30 min, metal concentration- 100 µg ml-1 and pH- 5.1 and 6, for Pb and Cd, respectively) however, the immobilized biomass of N. muscorum was found to be more suitable for the development of an efficient biosorbent as evident from theqmax(1000 mg g-1protein) and Kf (0.08 mg g-1protein) values obtained from the Langmuir and Freundlich isotherms. A pseudo second order kinetics was found more suitable for describing the nature of biosorption of both the metals by all the three forms of N. muscorum. An analysis of correlation revealed that as the metal concentration increases, the removal of Pb and Cd by N. muscorum also increases significantly. The regression analysis showed that the rate of removal of Pb by free living and dead biomass was 1.89 and 1.58 times higher than the rate of removal of Cd by respective biomass. In contrast, the rate of removal of Cd by immobilized biomass was 1.46 times higher than that of Pb.